The Ceremonials of the University Colleges. A Baroque Exemplification of the Student World - Ajenjo López, Pablo (CIAN-Revista de Historia de las Universidades, 2023)
This work aims to address the analysis of the ceremonials of several Spanish university colleges in the Modern Age. We propose a comparative line of work of the normative corpus of several colleges associated with the University of Salamanca, showing a relationship between them and the baroque world in which they are framed in order to understand the power that the college students acquired in the Castilian administration. Likewise, the analysis of several documents from the Papeles Varios section of the Archivo Histórico de la Universidad de Salamanca is incorporated, which serve as a reflection of the use and application of these ceremonies in the daily life of seventeenthcentury students.